Kinesiophobia, but not strength is associated with altered movement in women with patellofemoral pain - de Oliveira Silva, Danilo [UNESP]; Barton, Christian John; Briani, Ronaldo Valdir [UNESP]; Taborda, Bianca [UNESP]; Ferreira, Amanda Schenatto [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Azevedo, Fábio Mícolis de [UNESP] (Elsevier, 2019)
Background: Evidence indicates the presence of both kinesiophobia and knee extension strength deficits in women with patellofemoral pain (PFP). Both impairments may contribute to apparent compensatory gait patterns including reduced cadence and peak knee flexion during stair negotiation. Research question: Is kinesiophobia or knee extension strength associated with movement pattern in women with patellofemoral pain? Methods: Forty women with PFP were assessed with three-dimensional kinematic analyses during stair descent; isokinetic dynamometry of the knee extensors (isometric, concentric and eccentric); and the Tampa scale for kinesiophobia. Pearson coefficients were calculated to determine relationship among variables. Results: Kinesiophobia correlated significantly with cadence (r = −0.62, p < 0.001), and peak knee flexion (r = −0.76, p < 0.001). No significant correlations were found between any knee extensor strength variables and kinematics (cadence or peak knee flexion); or kinesiophobia (p > 0.05). Significance: Findings of this study could suggest addressing strength impairments alone may not adequately address kinesiophobia and movement pattern impairments in women with PFP. However, high-quality randomised controlled trials are needed to test this assumption. Further value may be added if currently evidence-based knee strengthening exercise is combined with education and/or graded exposure to address kinesiophobia, and consideration to gait retraining to address altered movement patterns at the knee.
Keywords: Anterior knee pain; Fear of movement; Kinematics; Psychosocial; Torque